Safety and Efficacy of Drug-Coated Balloons in Patients with Acute Coronary Syndromes and Vulnerable Plaque. (October 2022) - Zhang, Yu-Bin; Liu, Heng-Dao; Xing, Jun-Hui; Chen, Bo-Wen; Zhao, Yan-Yan; Gu, He-Ping; Tao, Hai-Long
Background: Percutaneous coronary intervention (PCI) is the main treatment option for acute coronary syndromes (ACS) often related to the progression and rupture of vulnerable plaques. While drug-eluting stents (DES) are now routinely used in PCI, drug-coated balloons (DCB) are a new strategy to PCI and their practice in the treatment of ACS with vulnerable plaques has not been reported. This study aimed to evaluate the safety and efficacy of DCB in ACS complicated with vulnerable plaque lesions. Methods: 123 patients were retrospectively analyzed and diagnosed with ACS and given PCI in our Cardiology Department from December 2020 to July 2022. Vulnerable plaques were confirmed by intravenous ultrasound (IVUS) in all patients. According to individual treatment plan, patients were entered into either DCB (n = 55) or DES (n = 68) groups. The results of coronary angiography and IVUS before and immediately after percutaneous coronary intervention were analyzed. The occurrence of major adverse cardiovascular events (MACE) and the results of coronary angiography were also evaluated during follow-up. Results: There were no significant differences in baseline clinical characteristics, preoperative minimal luminal diameter (MLD), and preoperative diameter stenosis (DS) between the two groups. Also, there were no differences in IVUS plaque burden (PB), vessel area, and lumen area in the two groups before and immediately after PCI. The efficacy analysis showed that immediately after PCI, the DCB group had smaller MLD and higher degrees of lumen stenosis than the DES group ( P < 0.05). However, during follow-up, no significant differences in MLD and DS were seen in two groups; relatively, late loss in luminal diameter（LLL）in the DCB group was smaller ( P ＜0.05). Safety analysis showed that during follow-up, 9 patients developed restenosis after DCB implantation while restenosis occurred in 10 patients with DES treatment, no statistical difference in the incidence of restenosis in the two groups. Besides, there was no statistical difference in the incidence of major adverse cardiac events（MACE）during hospitalization and follow-up in the DCB group (7.3% (4/55)) and the DES group (8.8% (6/68)). Conclusion: DCB is safe and effective for ACS complicated with vulnerable plaque and has an advantage over DES in LLL.